L’acquisto a non domino tra diritto privato italiano e tendenze europee - Magri, Geo (Cultura giuridica e diritto vivente, 2020)
[Purchase from non-owner between Italian private law and European trends]. The article, after having analysed the different solutions adopted in the European legal systems with regard to the purchase in good faith of a movable property from a non-owner, focuses on art. 1153 of the Italian Civil Code, highlighting the peculiarities of this rule compared to similar ones contained in other European civil codes. In Italy, indeed, the bona fide buyer enjoys a rather extensive protection, which also protects the purchase of stolen goods, even in cases where the thief has sold them.